Conclusions - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
This research has explored the relationship between user satisfaction and design factors for office renovations considering energy efficiency. The findings of this research strongly support user-focused renovations of office buildings. My motivation for this research started from the consideration of comfort and satisfaction of building users and the focus on providing better and comfortable work environments for office users. The focus on user comfort and satisfaction is important, because literature shows that the increase of user satisfaction leads to the improvement of productivity and less absenteeism in workspaces. This research has been conducted by applying diverse research methods and analyses, such as monitoring the indoor climate of office buildings, interviewing architects and facility managers, conducting user surveys, and conducting statistical analyses. This chapter presents the conclusions by answering the main research question and corresponding sub-questions of each chapter. This chapter also includes the general conclusions highlighting the scientific contributions to the body of knowledge of the built environment and limitations of the research.